Faktor-Faktor yang Mempengaruhi Niat Mahasiswa Melakukan Tindakan Whistleblowing pada Kecurangan Akademik - Salfitri, Deanisa Puspa; Coryanata, Isma (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Whistleblowing is considered one of the effective ways to avoid and detect in revealing cheating in college. This study uses the Theory of Planned Behavior (TPB) to analyze the complex interaction between three main factors in whistleblowing, namely individual, situational, and organizational factors. This study used primary data through questionnaires obtained from 182 active students from various universities' in Indonesia. This study used data analysis assisted by SPSS 26 software. The findings prove that the factors analyzed in this study have an impact on students' intentions to whistleblowing academic cheating, both collectively and partially. The results of this study prove that the bystander effect does not influence students' choices to whistleblowing academic fraud. When there are more individuals around when fraud occurs, the likelihood of a potential whistleblower discouraging reporting the fraud they witness is higher. While anonymous reporting channels, moral intensity, and trust in leaders positively affect students' intentions to whistleblowing academic fraud.